INDUSTRY 4.0: glitter or gold? A systematic review - Pereira, Gustavo Bernardi; Santos, Adriana de Paula Lacerda; Cleto, Marcelo Gechele (Brazilian Journal of Operations & Production Management, 2018)
Publications on the fourth industrial revolution have skyrocketed since its establishment in 2011, both in academic and non-academic channels. Even though their measurable results have been published in non-academic material, especially among industry and business reports, within the academia it is still unclear how they are shown. This study aims to review and analyse the presence of industrial results within the academic context in a systematic manner by using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology. The findings indicate an increase trend of this type of publication within the academia and further directions are suggested.